2014
DOI: 10.1103/physrevb.90.054110
|View full text |Cite
|
Sign up to set email alerts
|

Complex antipolar2×4×22structure withPnmasymmetry in

Abstract: First principles calculations are done for a √ 2 × 4 × 2 √ 2 P nma structure, which has been recently discussed in several attempts to describe experiments in complex magnetoelectric perovskites and which experimentally was shown to compete with several ferroelectric phases. This makes these materials extremely attracting as switchers, starters, field-stimulated capacitors, high-voltage converters, transmitters, etc. The relative energies of the √ 2 × 4 × 2 √ 2 P nma structure have been calculated from first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Structure of the as-prepared samples was found to be orthorhombic Pnma similar to that reported for the BiFe 1-x Mn x O 3 solid solutions in the range of 0.15≤x≤0.40 synthesized under high pressure [10]. Combination of the antipolar displacements of bismuth and the ++--oxygen octahedral tilting results in a 2a p 4a p 22a p superstructure (a p ~ 4 Å is the pseudocubic unit-cell parameter) of the Pnma phase in BiFe 0.50 Sc 0.50 O 3 [24,25].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Structure of the as-prepared samples was found to be orthorhombic Pnma similar to that reported for the BiFe 1-x Mn x O 3 solid solutions in the range of 0.15≤x≤0.40 synthesized under high pressure [10]. Combination of the antipolar displacements of bismuth and the ++--oxygen octahedral tilting results in a 2a p 4a p 22a p superstructure (a p ~ 4 Å is the pseudocubic unit-cell parameter) of the Pnma phase in BiFe 0.50 Sc 0.50 O 3 [24,25].…”
Section: Introductionsupporting
confidence: 78%
“…Three types of the XRD patterns different in terms of splitting of the fundamental reflections were observed: rhombohedral (similar to that of BiFeO 3 ) at y≤0 25,. orthorhombic (similar to the antipolar polymorph of BiFe 0.50 Sc 0.50 O 3 [24]) at 0.30≤y≤0.60, and monoclinic (similar to that of BiScO 3 [37]) at y=0.70.…”
mentioning
confidence: 96%
“…We demonstrate the approach on a 35 % La-substituted Bi 1−x La x Fe 0.5 Sc 0.5 O 3 . This is a particular composition studied as a part of our systematic research of multiferroic properties of the Bi 1−x La x Fe 1−y Sc y O 3 perovskites obtained under extreme conditions [13,14]. Bi 0.65 La 0.35 Fe 0.5 Sc 0.5 O 3 crystalizes into a distorted perovskite structure with orthorhombic Pnma symmetry and exhibits a long-range magnetic ordering below T N ~ 220 K. The crystal and magnetic structures of the Bi 0.65 La 0.35 Fe 0.5 Sc 0.5 O 3 perovskite were fully characterized based on neutron diffraction data.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most studied composition of the BiFe 1−y Sc y O 3 series is that, corresponding to y = 0.50 [11]. It was revealed that two nonequivalent structures with the same Pnma space group are possible for BiFe 0.50 Sc 0.50 O 3 [11,20]. In addition, an annealing-stimulated polymorphic transformation has been found.…”
Section: Introductionmentioning
confidence: 99%